Unraveling the complexity of transcriptomic, metabolomic and quality environmental response of tomato fruit - D'Esposito, D.; Ferriello, F.; Molin, A.D.; Diretto, G.; Sacco, A.; Minio, A.; Barone, A.; Barone, A.; Cavella, S.; Tardella, L.; Giuliano, G.; Delledonne, M.; et al.
The environment has a profound influence on the organoleptic quality of tomato (Solanum lycopersicum)fruit, the extent of which depends on a well-regulated and dynamic interplay among genes, metabolites and sensorial attributes. We used a systems biology approach to elucidate the complex interacting mechanisms regulating the plasticity of sensorial traits. To investigate environmentally challenged transcriptomic and metabolomic remodeling and evaluate the organoleptic consequences of such variations we grown three tomato varieties, Heinz 1706, whose genome was sequenced as reference and two "local" ones, San Marzano and Vesuviano in two different locations of Campania region (Italy). Results: Responses to environment were more pronounced in the two "local" genotypes, rather than in the Heinz 1706. The overall genetic composition of each genotype, acting in trans, modulated the specific response to environment. Duplicated genes and transcription factors, establishing different number of network connections by gaining or losing links, play a dominant role in shaping organoleptic profile. The fundamental role of cell wall metabolism in tuning all the quality attributes, including the sensorial perception, was also highlighted. Conclusions: Although similar fruit-related quality processes are activated in the same environment, different tomato genotypes follow distinct transcriptomic, metabolomic and sensorial trajectories depending on their own genetic makeup.
Keywords: ENVIRONMENT; FRUIT QUALITY; METABOLOME; NETWORK; PLASTICITY; SENSORIAL ATTRIBUTES; SOLANUM LYCOPERSICUM; TRANSCRIPTOME